THE ROLE OF HUMAN CAPITAL IN ECONOMIC INNOVATION SYSTEMS - Myltykbayeva L.A.; Doskaliyeva B.B.; Beketova Kamar Nazarbekovna (Academic Journal of Physical and Chemical Sciences, 2020)
Growth dynamics of modern innovation and information economy, both global and local, is not determined by a simple increase in production in all sectors, and that part which is generated by a variety of innovative and qualitative changes in the production process of goods and services. Further intensification of the innovative process in recent decades due to the formation of a new type of economic development based on the continuous change of the production base, and the nature of the products with the continuous creation of fundamentally new technologies as well as new types of goods and services. In the context of globalization, tightening the competition in the world market actualizes the problem of innovation and quality competition. This innovation has become the main vector of economic development (Ivanov N., 2013). The purpose of our research is to define and reveal such notions as human capital, economic innovation, economic structure, economic development, productive capital, innovation, innovative process, economic growth, and labor force. The article directs to study and reveal the role, impact and significance of human capital for economic innovation and development, to find out and explain the notions of human capital theory and the origin of human capital. The main reason for this research is the growing awareness of the fact that human resources and their interconnection are crucial for the activities of any entity, be it a firm, nation, economy or global economy. In their search, scientists tried to obtain an objective understanding of these concepts and compare these soft forms of capital with the traditional idea of capital as a factor of production in the economy. Continuing education and activization of creative opportunities concerns not only individual employees, but the team as a whole. It is about the formation of the intellectual capital of the company, as part of its intangible assets. The intellectual capital of the company and the country as a whole becomes a prerequisite for the inclusion of companies and countries in the global economy with the greatest benefit for the country and the standard of living of its citizens. The intellectual capital of the company and the country as a whole becomes a prerequisite for the inclusion of companies and countries in the global economy with the greatest benefit for the country and the standard of living of its citizens. The human factor determines the country’s competitiveness in the global economic system. Studies have led to the conclusion that the basis of modern competitive countries is the availability of innovative systems and human resources.